Digitalization of the Economy and Its Impact on SME Competitiveness in Emerging Markets - Tia Julaeha; Alejandro Díaz Pelaez (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Digitalization has become a critical driver of economic transformation, particularly in emerging markets where small and medium enterprises (SMEs) play a central role in economic development. This study aims to analyze the impact of digitalization on SME competitiveness by synthesizing empirical evidence from recent academic literature. The research adopts a qualitative systematic literature review approach, examining peer-reviewed journal articles published between 2023 and 2025. The findings indicate that digitalization significantly enhances SME competitiveness through improved operational efficiency, market expansion, innovation capability, and customer engagement. However, structural barriers such as limited digital infrastructure, low digital literacy, and regulatory constraints hinder optimal adoption. The study also finds that digital strategy and innovation act as mediating factors that strengthen the relationship between digital adoption and firm performance. The results highlight the importance of integrated policy frameworks and strategic digital capabilities in fostering sustainable competitive advantages. This research contributes to the literature by providing a comprehensive synthesis of digital transformation impacts in emerging economies and offers practical implications for policymakers and SME stakeholders.